Report of the Conference of Ministers of Agriculture of the Americas 2023 – Twenty-second Regular Meeting of the Inter-American Board of Agriculture - Inter-American Board of Agriculture (IABA) (Instituto Interamericano de Cooperación para la Agricultura (IICA), 2024)
The 2023 report of the Inter-American Board of Agriculture (JIA) addresses various essential topics for agricultural cooperation and development in the Americas region. A study has been initiated to review and update the regulations of the IICA Directorate General regarding human resources and financial operations, with the aim of aligning them with technological advancements and the current needs of the Institute. This review also seeks to reflect changes in administrative practices implemented since 1983. The conference included participation from rural leaders from several countries, as well as representatives from public and private organizations who discussed the transformation of agri-food systems through public-private partnerships. The agenda included the review of the 2024-2025 program-budget, the assessment of progress in various projects, and the planning of future initiatives. Visits to IICA facilities were also conducted to showcase technological advancements and innovative agricultural practices. Several resolutions were approved to support the regulatory review study and authorize the Executive Committee to implement the necessary modifications, aiming to improve the administrative efficiency and effectiveness of IICA. This report underscores the commitment of the Member States and IICA to sustainable development and the modernization of agriculture in the region, promoting cooperation and innovation as fundamental pillars.